Curving resistance from wheel-rail interface. Issue 3 (4th March 2022) - Wu, Qing; Wang, Bo; Spiryagin, Maksym; Cole, Colin
Abstract : This paper uses vehicle system dynamics simulations to investigate curving resistance generated from the wheel-rail interface. More than 600 simulations were conducted using a freight wagon model to investigate the implications of curve radii, vehicle speeds and track superelevation for curving resistance, as well as the changes of curving resistance with wheelset Angle of Attack (AoA) and track cant deficiency. The results show that with the same curve radius, vehicle speeds and track superelevation can change the simulated curving resistance by 13–26%. Comparatively, vehicle speeds have stronger influences; resistance variations due to speed changes were about 16% larger than those due to superelevation changes. When the speed of the specific wagon was lower than 60 km/h, curving resistance decreases with both the increase of speed and the decrease of track superelevation. However, these trends can change to their opposite directions when speed reaches 70 or 80 km/h. Curving resistance increases with the increase of AoA and with the decrease of curve radii. The analyses of cant deficiency show that overbalanced speed cases generally have lower curving resistance. The results of the specific wagon indicated that zero cant deficiency did not generate the minimum curving resistance.